ANALYSIS OF COMPERATIVE LANGUAGE STYLE AND LINKING LANGUAGE STYLE ON THE CARS 1 MOVIE SCRIPT - Fernando Sahat Halomoan Rajagukguk; Rina Octavia Simarmata; Harpen H. P. Silitonga (Sean Institute, 2023)
This research aims to describe: (1) What language styles are used in the movie